The Implementation of Gender Mainstreaming in ASEAN - Athiqah Nur Alami (IKAT: The Indonesian Journal of Southeast Asian Studies, 2018)
Studies on gender mainstreaming in Southeast Asia, with its diverse socio-political background of its member states, are still under-explored. This paper examines the implementation of gender mainstreaming in the Association of Southeast Asian Nations (ASEAN). Meanwhile, the region has shown its considerable economic growth and rapid development of human rights issue in the last decades. The study finds that ASEAN has shown its initiatives across different stages of gender mainstreaming. By the adoption of gender mainstreaming concept, ASEAN has made institutionalization of gender issues and also has produced and implemented extensive gender mainstreaming policies. However, there are constraints on each stage, which mostly are about conforming gender equality agenda to organizational mandates as well as lacks of supporting systems such as data, human resources, and funding. Even though this paper agrees on the long-term nature of gender mainstreaming strategy, the implementation of the strategy in ASEAN should be effectively improved and consistently maintained to fulfill the goals of ASEAN Community.